Analisis Yuridis terhadap Tenaga Kerja Asing “Tiongkok” yang Dipekerjakan di Kota Batam Ditinjau dari Hukum Ketenagakerjaan - Agustianto Agustianto; Rodeen Chenggaliex Chenggaliex (Journal of Judicial Review, 2017)
This writing discusses the problems of foreign workers employed by employers in terms of labor law. The purpose of this study is to find out the problems that occur to the foreign workers "Tiongkok" who are employed in the city of Batam and the steps that can be used employers and governments in maximizing the use of foreign workers. This research is an empirical juridical research using descriptivequalitative method. The data used in the form of primary and secondary data, collected by way of study keperpustakaan and research in the field. After all the data collected, then the data is then processed and analyzed qualitatively, which means by grouping data aspects studied. The following conclusions are drawn to this research, then described descriptively. Based on this research, it is found that from the Regulation of the Minister of Manpower, the employers of foreign workers and foreign workers must have a permit to use foreign workers, permit to employ foreign workers and wire recommendations, as well as sanctions against the parties to violate the applicable regulations. Governments should play a more active role in granting licenses to foreign workers, and employers should clarify procedures and requirements that foreign workers must possess clearly so that foreign workers know that they are qualified workers and procedures With Indonesian regulations.